Кекси з гарбузом на основі безглютенового борошна - Басай, Олексій Сергійович; Павлюченко, Олена Станіславівна (My University, 2017)
Проведені дослідження вибору оптимального співвідношення компонентів композиційних сумішей: кукурудзяне: рисове та кукурудзяне: вівсяне борошно у рецептурі кексів з гарбузом. Studies have been conducted to select the optimal ratio of the components of composite mixtures: corn: rice and corn: oat flour in the recipe of cupcakes with pumpkin.
Keywords: вівсяне борошно; органолептичні показники; безглютенові кекси; гарбуз; рисове борошно; кукурудзяне борошно; gluten-free muffins; pumpkin; organoleptic indicators; rice flour; corn flour; oat flour; кафедра технології ресторанної і аюрведичної продукції